«Charme, zur Haltung gemacht»: lectura de un texto de Frisch desde Schiller - Barjau, Eustaquio (Revista de Filología Alemana, 2002)
This article is divided into two main sections. The first section is aimed at studying the relations bearing between literature and philosophy. More particularly it examines the ways in which philosophy contributes to the understanding of a literary text. The focus is then placed on Max Frisch’s aphorism «Charme, zur Haltung gemacht», as seen from Schiller’s essay «Über Anmut und Würde», to confirm the points these writings have in common. Most notably, both Frisch and Schiller higlight the incompatibility between charm itself and the will to charm. In the second section Frisch’s text is examines under the philosophical categories of ‘truth’, ‘nature’ and ‘spirit’.